Herding Behavior in Indonesian Investors - Sumani; Fransiska, Maria; Willy; Pangestu, Stevanus (Universitas Prasetiya Mulya, 2018)
This research attempts to investigate the herding behavior of the companies that invested in IDX LQ45 Index during 2014 through 2016. Herd behavior is the tendency of investors to follow other investors’ actions in the market. LQ45 was chosen as it comprises the most heavily-traded stocks of the Indonesian Stock Exchange. This research used Vector Autoregressive model to determine the effects of size and market return on the herding behavior. The Granger causality test suggests that there are dynamic interactions: (i) between size and herding behavior; and (ii) between market return and herding behavior. In addition, Variance Decomposition and Impulse Response reveal that market capitalization (size) has variable of the greater role in defining herding behavior, compared to that of market return.